Digital transformation, green technology innovation and corporate value - Zhang, Lijuan; Song, Zirui (Frontiers in Environmental Science, 2025)
One of the key factors influencing corporate sustainable development is green technology innovation (GTI). Our study intends to explore how digital transformation impacts corporate value through GTI. We use panel data from A-share publicly listed firms in China spanning from 2012 to 2022 as our sample. We employ textual analysis to extract keywords correlated to digital transformation from the annual reports, and construct an indicator to evaluate the digital transformation of corporates. Our findings show that digital transformation significantly enhances enterprise value by improving green technology innovation. Furthermore, the market competition and green credit moderate the mediated relationship between digital transformation and corporate value. Additionally, heterogeneity tests indicate that digital transformation has a more significant influence on value enhancement for heavily polluting corporates, non-high-tech corporates, and smaller corporates. This research offers important recommendations for practitioners on advancing sustainable business practices and provides policy recommendations for environmental protection and green development.